IN VITRO AND IN SILICO ANTIBACTERIAL ACTIVITIES OF Syzgium aromaticum ESSENTIAL OIL AGAINST BACTERIA ASSOCIATED WITH OTITIS MEDIA IN CHILDREN - OBUOTOR , Tolulope Mobolaji; ADEYANJU, Folasade Oluwademilade; KOLAWOLE, Amos Oyebisi; IDOWU, Gbohunmi Paul; OLUWAMUYIWA, Fesobi Andrew; AFOLABI, Felix Olaide (African Journal of Infectious Diseases (AJID), 2022)
Background: This study investigated the efficacy of the essential oil (EO) of Syzgium aromaticum L. (clove) on the bacteria associated with otitis media. Materials and Methods: Ear swab samples were collected and bacteria isolated were identified using morphological and biochemical procedures. Essential oil was extracted from the dried flower buds using the hydro-distillation method while physicochemical and phytochemical analysis was done on the oil. Antibiotic susceptibility test and agar well diffusion was used to determine the susceptibility of the isolates to the EO. In – silico analysis was conducted to determine the drugable compound in the EO. Results: Phytochemical analysis of the oil indicated the presence of flavonoids, sterols, phenols, carbohydrates and alkaloids. Physicochemical test of the EO exhibited the presence of eugenol (80.98%) as the most abundant phytocompound. Percentage occurrence of the bacterial isolates are as follows; Proteus mirabilis (31.25%), Staphylococcus aureus (25%), Pseudomonas aeruginosa (18.25%), Proteus vulgaris (3.12%), Moraxella catarrhalis (12.5%), Klebsiella pneumoniae (3.12%) and Staphylococcus epidermidis (6.25%). Zones of inhibition were within the range of 11.5±0.71mm-23.0±2.83mm. In silico studies demonstrated that 16 out of 38 compounds identified passed the ADMET analysis. Various compounds had different binding energies, such as linalool, carvacrol for S. aureus (2NOJ), gamma-eudesmol, eudesmol for Proteus mirabilis (6H2L), eucalyptol, gamma-eudesmol and eudesmol for Proteus vulgaris (4MCX) and Staphylococcus epidermidis (4HBL). Conclusion: This study shows the potency of clove EO as an antibacterial agent and its component as potential lead molecules in drug development and design to combat multi – drug resistance.